Functional Properties of Soy Yoghurt with Red Dragon Fruit Substitution - Marjan, Avliya Quratul; Mustika, Nurul; Fatmawati, Iin; Arini, Firlia Ayu (Jurnal Gizi dan Pangan, 2023)
This study investigated the antioxidant activity and lactic acid bacteria content of soy yoghurt with red dragon fruit substitution. Analysis included sensory evaluation, proximate analysis, quantification of antioxidant activity and estimation of total Lactic Acid Bacteria (LAB). Formula 3 with 35% red dragon fruit substitution was selected as the optimal formula. Proximate analysis showed water content of 92.75%, ash content of 0.23%, protein content of 0.48%, fat content of 3.08%, and carbohydrate content of 3.46%. The selected product had an increased antioxidant activity. In conclusion, soyghurt with red dragon fruit can increase the antioxidant activity of the product.